(123)I-MIBG Scintigraphy in the Subacute State of Takotsubo Cardiomyopathy - Christensen, Thomas Emil; Bang, Lia Evi; Holmvang, Lene; Skovgaard, Dorthe Charlotte; Oturai, Ditte Bang; Søholm, Helle; Thomsen, Jakob Hartvig; Andersson, Hedvig Bille; Ghotbi, Adam Ali; Ihlemann, Nikolaj; Kjaer, Andreas; Hasbak, Philip (JACC. Cardiovascular imaging, 2016)
The study sought to investigate adrenergic activity in patients with takotsubo cardiomyopathy (TTC). TTC is a specific type of reversible heart failure possibly caused by excessive catecholamine stimulation of the myocardium. Scintigraphic iodine-123-meta-iodobenzylguanidine (mIBG) imaging of the heart and measurement of plasma catecholamines can be used to assess adrenergic activity in vivo. The authors hypothesized that sympathetic nerve activity is increased in the subacute state of TTC, and this study used cardiac mIBG imaging and plasma levels of norepinephrine and epinephrine as markers to assess this hypothesis. In this study, 32 patients with TTC and 20 controls were examined at admission and again on follow-up with echocardiography, mIBG scintigraphy, and plasma catecholamine measurements. Ejection fraction (EF) was initially 36 ± 9% but increased to >60% (p = 0.0004) in all patients with TTC. In the control subjects EF was initially higher (51 ± 11%; p = 0.0004) than in the patients with TTC. However, EF of the patients with TTC exceeded that of the control subjects on follow-up (56 ± 8%; p = 0.0007). The mIBG imaging showed a lower late (4-h) heart-to-mediastinum ratio (H/Mlate) (2.00 ± 0.38) and a higher washout rate (WR) (45 ± 12%) in the subacute state of TTC, both when compared with follow-up (H/Mlate: 2.42 ± 0.45; p = 0.0004; WR: 33 ± 14%; p = 0.0004) and when compared with the control group in the subacute state (H/Mlate: 2.34 ± 0.60, p = 0.035; WR: 33 ± 19%, p = 0.026). On follow-up, no differences in mIBG parameters were observed between the TTC and control groups (H/Mlate: 2.41 ± 0.51, p = 0.93; WR: 30 ± 13%, p = 0.48) group. In the TTC group, plasma epinephrine levels were elevated in the subacute state (Log2[epinephrine]: 6.13 ± 1.04 pg/ml), both when compared with follow-up (5.25 ± 0.62 pg/ml; p = 0.0004) and when compared with the control group in the subacute state (5.46 ± 0.69 pg/ml; p = 0.044), and these levels remained elevated in the TTC group on follow-up compared with the control group (4.56 ± 0.95 pg/ml; p = 0.014). No significant differences in plasma norepinephrine levels were observed. The present study supports a possible role of adrenergic hyperactivity in TTC.